Subproductos del cacao (Theobroma cacao) como alternativa para la mejora de la dieta balanceada en rumiantes - García Villoslada, A. E. (2022)
Cocoa production is estimated at 4.7 million tons per year, of which 90% are waste residues, such as cocoa husks (CC). These agricultural by-products are a source of nutritional compounds of interest to the ruminant sector. Studies carried out on this matter have shown that it has a high percentage of proteins, fiber, phenols, among others, which give it nutraceutical properties. The fiber present in CC has the potential to absorb oils and cholesterol, thus reducing its bioavailability during digestion. Therefore, the objective of this research was to describe and analyze the nutritional properties of cocoa by-products in the induction of a balanced diet for ruminant animals. The analysis was performed by searching the literature review (Scopus, Scielo) during the months of April and May 2022, the guidelines of the PRISMA statement were followed and to establish the search string, the Boléan operators were used. Current evidence suggests the use of cocoa by-products as an alternative for the improvement of the balanced diet in ruminants (under relevant parameters), as a non-conventional alternative raw material in diets for the ruminant sector for its contribution in protein and fiber that helps fattening without detrimental effects on milk production performance